Seismic Imaging of Halokinetic Sequences and Structures With High‐Resolution, Dual‐Element Acquisition, and Processing: Applications to the Gassum Structure in Eastern Jutland, Denmark - M. Westgate; K. Kucinskaite; E. Konstantinidis; A. Malehmir; M. Papadopoulou; U. Gregersen; M. Keiding; M. Bjerager (Earth and Space Science, 2025)
Abstract Understanding the structural intricacies of subsurface halokinetic formations is crucial for various geological applications, including geological capture and storage (geological carbon storage (GCS)). This study focuses on the seismic imaging of the Gassum structure in eastern Jutland, Denmark, employing high‐resolution, dual‐element acquisition, and processing techniques. The investigation aims to unravel details in the evolution of the salt dome and its implications for GCS potential. High‐resolution seismic data processing and interpretation reveals a skewed dome structure with steeper flanks on the western and northern sides, characterized by faults and stratigraphic thinning. The asymmetric growth of the dome suggests uneven salt loading during its genesis, influencing local stress fields and structural development, with evidence of syn‐tectonic subsidence that produced salt welds. This is supported by the presence of stratigraphic wedges and an increased depth of imaged horizons within steeper flanks of the dome. A mild piercement of the salt into overlying sediments, onlapping features, and the presence of normal faults that originate from the dome apex and extend radially, all indicate a reactive piercement process in the salt pillow's development stage. This produced an extensional regime in overlying strata, inducing sequence thinning and graben structures. Analysis of reservoir and seal properties unveils adequate conditions for GCS, with a continuous reservoir and thick primary and secondary seals. However, the presence of faults intersecting these formations raises concerns regarding long‐term storage stability. Further investigations into reservoir porosity, migration paths, and volumetric analysis are warranted for conclusive GCS assessments.